Traditional Chinese Medicine for Bradyarrhythmia: Evidence and Potential Mechanisms - Liu, Shuo; Tian, Guihua; Chen, Jing; Zhang, Xiaoyu; Wu, Aiming; Li, Min; Sun, Yang; Liu, Baoshan; Xing, Yanwei; Shang, Hongcai (Frontiers in Pharmacology, 2018)
Importance: The incidence of Bradyarrhythmias is high among the population. However, at early stages of the disease, it cannot always get enough attention and is lack of safe and effective therapies, until it is serious enough to resort to pacemaker implantation. Traditional Chinese Medicine (TCM) has a long history of treating Bradyarrhythmia, with a lot of formulas being widely used in clinical practice. While the effectiveness and the underlying mechanisms of these formulas have not yet been clearly identified. Objective: To evaluate the effectiveness of some common TCM formulas in treating patients with Bradyarrhythmia and to summarize the current evidence as to their mechanisms. Data Sources: Relevant studies were identified by searching for papers published from January 2000 to August 2017 in Pubmed; EMBASE; the Cochrane Library (Cochrane Central Register of Controlled Trials); the China National Knowledge Internet; and the China biology medicine, Wanfang, and VIP databases. The following medical subject heading (MeSH) terms were included for Pubmed search and adapted for other databases as needed-“Medicine, Chinese Traditional,” “Bradycardia.” Study Selection: Randomized clinical trials investigating treatment outcomes in Bradyarrhythmia patients with one of the six TCM formulas (Shenxian-shengmai oral liquid, Shensong Yangxin capsule, XinBao pill, Mahuang-Fuzi-Xixin decoction, Zhigancao decoction and Shengmai injection). Data Extraction and Synthesis: Two independent reviewers performed the data extraction and assessed study quality. A meta-analysis was performed to calculate risk ratio (RR) and 95% confidence index (CI) using random-effects and fixed-effects model. Results: A total of 121 clinical trials with 11138 patients were included. Of the six TCM formulas, SXSM (RR:1.33, 95% CI 1.27 to 1.39, P < 0.00001), SSYX (RR:1.52, 95% CI 1.40 to 1.66, P < 0.00001), XB can be more effective than common treatment (RR 1.18, 95% CI 1.11 to 1.26, P < 0.00001), as well as placebo (RR 5.33, 95% CI 2.88-9.87, P < 0.00001), but less effective than TCM dialectical therapy (RR:0.75, 95% CI 0.68 to 0.82, P < 0.00001). Compared to the control group, MFX (RR:1.30, 95%CI 1.23 to 1.37, P < 0.00001), ZGC (RR:1.35, 95%CI 1.23 to 1.48, P < 0.00001), SMI (RR:1.36, 95%CI 1.21 to 1.52, P < 0.00001) can be more effective. The overall quality of the included trials were relatively low, with the limitations of small sample size, inadequate descriptions in randomization, allocation concealment and blinding methods. Conclusions and Relevance: There are evidence that some TCM formulas might help to relieve Bradyarrhythmias. But with the relatively low quality of the clinical trials and mechanism studies, we still need more high-quality researches to verify the conclusions.